Intraventricular hemorrhage in very low birth weight neonates and risk factors: experience of a Peruvian hospital - Feijóo-Ocorima, Melissa Johana (2025)
Introduction: Intraventricular hemorrhage (IVH) affects the subependymal germinal matrix, and usually presents between 3 and 4 days of life. Fifty percent of cases occur on the first day and are diagnosed by cranial ultrasound. Affected neonates may develop neurodevelopmental alterations and even die. Objective: To identify the factors associated with intraventricular hemorrhage in very low birth weight newborns in a Peruvian hospital. Material and Methods: Analytical, case-control study. Information was obtained from virtual medical records and analyzed by descriptive and analytical statistics (chi-square or Fisher's exact test, crude and adjusted OR); a sample calculation and goodness-of-fit test were previously performed. Results: 204 neonates were included (55 cases and 149 controls). The most frequent HIV grades were I and II. In logistic regression, the significantly associated factors were vaginal delivery (aOR = 3.37, 95% CI [1.18 - 9.62], p = 0.023) and use of mechanical ventilation (aOR = 6.95, 95% CI [1.29 - 37.30], p = 0.024). Such association with HIV would be explained by stress and trauma, which condition fluctuations in cerebral blood supply, generating damage to the neonate's developing blood vessels, thus triggering bleeding. Conclusions: The prevalence of HIV in very low birth weight neonates is considerable. Associated factors identified include vaginal delivery and the use of mechanical ventilation.